Ostracode species census data for DSDP Leg 94 sites - Thomas M Cronin; Maureen E Raymo; K P Kyle (PANGAEA, 1996)
Ostracode assemblages from Deep Sea Drilling Project Sites 607 (western Mid-Atlantic Ridge) and 610 (southeast Rockall Plateau) show rapid, systematic shifts during late Pliocene glacial-interglacial cycles that reflect deep-sea environmental change. Progressive decreases in North Atlantic deep-water taxa and increases in Southern Ocean taxa occur from 3.4 to 2.4 Ma, and high-amplitude faunal cycles begin near 2.8 Ma. Four ostracode assemblages, each with a characteristic phase relative to 41 k.y. obliquity glacial-interglacial d18O cycles, characterize the benthic faunal record at Site 607. Cross-spectral analysis shows that the Site 607 glacial assemblage has a 41 k.y. periodicity significant at the 95% level; other assemblages show a less significant, but still obvious, concentration of variance at 41 k.y. Faunal patterns suggest climatically controlled reorganization of deep-sea benthic communities during glacial-interglacial cycles due to oscillating deep-sea environments.
Supplement to: Cronin, TM et al. (1996): Pliocene (3.2-2.4 Ma) ostracode faunal cycles and deep ocean circulation, North Atlantic Ocean. Geology, Aug 1996; 24:, 24, 695-698, https://doi.org/10.1130/0091-7613(1996)024%3C0695:PMOFCA%3E2.3.CO;2